Preparation and application of specific chicken yolk antibodies in detecting Brucella - Qi, Xinru; Zhao, Shiqi; Huang, Qianhan; Wang, Yun; Pei, Qichuan; Chen, Yixiao; Yin, Dehui; Zhan, Tiansong (Frontiers in Veterinary Science, 2025)
Brucellosis, caused by Brucella, is a severe zoonotic disease. Conventional IgG antibody-based ELISA testing faces challenges such as false positives and cross-reactivity. In this study, three specific chicken yolk antibodies (IgY) targeting Brucella were isolated from the eggs of immunized hens, and a method for detecting Brucella utilizing these antibodies was developed and subsequently compared to traditional IgG antibodies. These IgY antibodies were generated against a fusion protein, LPS, and whole-cell antigen, and their potency was evaluated through indirect ELISAs. Testing was conducted to assess cross-reactivity, limit of detection, and detection in simulated samples. The IgY antibodies demonstrated high potency and no cross-reactivity with common foodborne pathogens. Both LPS-IgY and Brucella-IgY showed excellent detection capabilities in identifying Brucella, particularly in food samples. These results underscore the potential of using LPS-IgY and Brucella-IgY antibodies as replacements for conventional IgG antibodies in Brucella detection, especially in the realm of food safety. The implications of this study are significant, as it presents a promising alternative approach for detecting Brucella in food products, thereby reducing the risk of transmission and ensuring public health and safety.